Analisis Manajemen Tenaga Pendidik dalam Hal Linearitas di MTs Negeri 5 Subang - Windy Surya Nirwani (Jurnal Manajemen Pendidikan Islam (MANAPI), 2025)
This research aims to analyze the management practices of educators at MTs Negeri 5 Subang, particularly concerning the issue of linearity between teachers' academic backgrounds and the subjects they teach. The method used is a descriptive qualitative approach with data collection techniques through semi-structured interviews with leaders and teachers of the madrasah. The results show that the centralized teacher recruitment system through CPNS results in limitations in meeting the specific needs for teachers. The phenomenon of non-linearity causes some teachers to handle subjects outside their area of expertise, which has the potential to reduce the quality of learning. Although the madrasah has implemented periodic training, performance evaluations, and professional development based on SKP, challenges regarding competency mismatches remain a strategic issue.